A New Species of Baurubatrachus (Anura, Neobatrachia) from the Late Cretaceous Adamantina Formation of Brazil Furnishes Evidence on the Diversity of this Bizarre Genus - Muzzopappa, Paula (2022)
In the present paper, we report new anuran remains recovered from strata referred to the Adamantina Formation (Upper Cretaceous) cropping out near Catanduva city, São Paulo, Brazil. The remains represent two individuals, one of which bears a set of peculiar characteristics, both cranial and postcranial, that allows us to assign them to the already known genus Baurubatrachus. To date, the genus was only represented by the holotype of Baurubatrachus pricei, recovered from the Upper Cretaceous Serra da Galga Formation (which is younger than the Adamantina Formation), near Peirópolis (Minas Gerais, Brazil), 200 km north of Catanduva City. The lesser ossification as well as the slender configuration of the scapula and ilia of the new remains, relative to B. pricei, points to the identification of a new species, Baurubatrachus santosdoroi sp. nov. The detailed study of the peculiar anatomy of these specimens provides new osteological features for the genus, such as the presence of a subtympanic foramen, as well as new character states for other traits to be considered in future systematic studies.